Dual‐Site Functionalization on Supported Metal Monolayer Electrocatalysts for Selective CO2 Reduction. Issue 3 (27th November 2022) - Zhao, Zhonglong; Lu, Gang
Abstract: Development of efficient catalysts for electrochemical carbon dioxide reduction reaction (CO2 RR) represents a great challenge in renewable energy research. Although noble metals have long been explored as catalysts for CO2 RR, their reactivity and selectivity remain rather low owing to the competing hydrogen evolution reaction (HER). Here, this work proposes that noble metal monolayers (MLs) supported by transition metal carbides (TMCs) and nitrides (TMNs) can become exceptional CO2 RR catalysts with much suppressed HER. This work shows that there is a direct, antibonding interaction between the hydrogen adsorbate and the TMC/TMN substrates, while such interactions between CO2 RR intermediates and the substrates are absent. This difference enables dual‐site functionalization of the ML catalysts, which circumvents the energy scaling relations dictating the competition between CO2 RR and HER. Consequently, it is possible to reduce the binding of the H adsorbate to suppress HER and simultaneously increase the binding of CO2 RR intermediates to boost the CO2 RR. This work identifies several Ag and Au‐based catalysts that are thermodynamically and electrochemically stable and exhibit high activity and selectivity toward the production of formic acid. In addition, this work predicts that higher order CO2 RR products including methanol and ethylene can also be produced on selected catalysts. Abstract : Based on first‐principles calculations, it is predicted that noble metal monolayers supported by transition metal carbides (TMCs) and nitrides (TMNs) could be highly selective catalysts for CO2 electroreduction with suppressed hydrogen evolution. Dual‐site functionalization induced by an antibonding interaction between hydrogen and the TMC/TMN substrates is identified, which can circumvent energy scaling relations and enable active, selective, and robust CO2 electroreduction.